Petrogenesis and geotectonic significance of magnesian andesite in the Nangunyuan area, northern Hainan Island, China - Lin, Yihua; Liang, Dingyong; Hu, Zailong; Yuan, Qinmin; Lv, Zhaoying; Guan, Jun (Frontiers in Earth Science, 2025)
The Magnesian andesite discovered in the Nangunyuan area of northern Hainan Island provides an important research object for constraining the tectonic evolution process of the Paleo-Tethys Ocean in Southeast Asia. The formation age of the Magnesian andesite in the Nangunyuan area of northern Hainan Island was determined to be 251.2 ± 4.5 Ma in the late Permian by LA-ICP-MS zircon U-Pb dating. The Magnesian andesite is characterized by relatively high contents of SiO2, CaO, and MgO, and relatively low contents of Na2O, K2O, and FeO. It is enriched in large ion lithophile elements and relatively depleted in high field strength elements, with obvious negative anomalies of Ta, Nb, and Ti. It has geochemical characteristics similar to those of Sanukite and belongs to island arc volcanic rocks. The Magnesian andesite may be formed by the equilibrium reaction between the mantle peridotite and the Si-rich melt from the partial melting of the subducting oceanic crust slab or sediment. It is the product of the wedge mantle source region of the Changjiang-Qionghai tectonic belt affected by the metasomatism of the subduction component. Its formation age is close to the closure time of the Paleo-Tethys Ocean, which may mark the late stage of the subduction of the Paleo-Tethys Ocean. The discovery of the late Permian Magnesian andesite in northern Hainan Island reveals the late-stage dynamics of the subduction of the Paleo-Tethys Ocean. Its magma source mixing origin reflects the complex interactions between the crust and mantle in the subduction zone. This discovery is of great scientific value for constraining the closure time of the Paleo-Tethys Ocean, understanding the formation mechanism of the Paleo-Tethys orogenic belt, and regional metallogeny.